Iron oxide catalyst at the modified glass fiber support for selective oxidation of H2S; Catalysis Communications; Vol. 87 - Mikenin P.; Zazhigalov S.; Elyshev A.; Lopatin S.; Larina T.; Cherepanova S.; Pisarev D.; Baranov D.; Zagoruiko A. N. Andrey Nikolaevich (2016, 2016)
Title screen